2005
DOI: 10.1038/sj.npp.1300813
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Rolipram Delivery Activates Hippocampal CREB and Arc, Enhances Retention and Slows Down Extinction of Conditioned Fear

Abstract: Rolipram, a type IV-specific phosphodiesterase inhibitor, is known to improve memory under various learning tasks. Moreover, Rolipram treatments have been shown to increase expression and phosphorylation of a key factor for hippocampal memory consolidation, the cAMP-dependent response element-binding protein, CREB. However, the exact correlation between hippocampal CREB phosphorylation and memory improvement induced by Rolipram has not yet been determined in a CREB-dependent type of hippocampal-related learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 63 publications
(86 reference statements)
1
72
0
Order By: Relevance
“…Moreover, subchronic delivery of rolipram in rats has been shown to slow extinction of conditioned fear (Monti et al, 2006). Similarly, McNally et al (2005) found that administration of the cAMP analog 8-Br-cAMP impaired extinction, although PKA activation by Sp-cAMPs had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subchronic delivery of rolipram in rats has been shown to slow extinction of conditioned fear (Monti et al, 2006). Similarly, McNally et al (2005) found that administration of the cAMP analog 8-Br-cAMP impaired extinction, although PKA activation by Sp-cAMPs had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Monti et al 282 reported that rolipram, a phosphodiesterase inhibitor that increases cAMP concentrations in the brain, facilitates acquisition of fear and delays extinction. In these experiments, rats were implanted with osmotic minipumps that released rolipram or vehicle steadily for 7 days.…”
Section: Neurotransmitter Systemsmentioning
confidence: 94%
“…Subsequent work supported a role for PDE4 in learning and memory processes (59), including activation of cAMP/PKA/CREB signaling and facilitation of longterm potentiation (LTP) in the hippocampus (60,61). Furthermore, rolipram reverses MK801-induced cognitive deficits in radial arm maze (62) and passive avoidance tests (63).…”
Section: Effects Of Pde4 Inhibitors On Dopamine-related Behaviormentioning
confidence: 99%